Complex effects of eslicarbazepine on inhibitory micro networks in chronic experimental epilepsy. (16th January 2021) - Schmidt, Sarah; Pothmann, Leonie; Müller‐Komorowska, Daniel; Opitz, Thoralf; Soares da Silva, Patrício; Beck, Heinz
Summary: Objective: Many antiseizure drugs (ASDs) act on voltage‐dependent sodium channels, and the molecular basis of these effects is well established. In contrast, how ASDs act on the level of neuronal networks is much less understood. Methods: In the present study, we determined the effects of eslicarbazepine (S‐Lic) on different types of inhibitory neurons, as well as inhibitory motifs. Experiments were performed in hippocampal slices from both sham‐control and chronically epileptic pilocarpine‐treated rats. Results: We found that S‐Lic causes an unexpected reduction of feed‐forward inhibition in the CA1 region at high concentrations (300 µM), but not at lower concentrations (100 µM). Concurrently, 300 but not 100 μM S‐Lic significantly reduced maximal firing rates in putative feed‐forward interneurons located in the CA1 stratum radiatum of sham‐control and epileptic animals. In contrast, feedback inhibition was not inhibited by S‐Lic. Instead, application of S‐Lic, in contrast to previous data for other drugs like carbamazepine (CBZ), resulted in a lasting potentiation of feedback inhibitory post‐synaptic currents (IPSCs) only in epileptic and not in sham‐control animals, which persisted after washout of S‐Lic. We hypothesized that this plasticity of inhibition might rely on anti‐Hebbian potentiation of excitatory feedback inputs onto oriens‐lacunosum moleculare (OLM) interneurons, which is dependent on Ca 2+ ‐permeable α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptors. Indeed, we show that blocking Ca 2+ ‐permeable AMPA receptors completely prevents upmodulation of feedback inhibition. Significance: These results suggest that S‐Lic affects inhibitory circuits in the CA1 hippocampal region in unexpected ways. In addition, ASD actions may not be sufficiently explained by acute effects on their target channels, rather, it may be necessary to take plasticity of inhibitory circuits into account.